EDUKASI FISIOTERAPI PADA IBU HAMIL PRENATAL DAN PASCANATAL DI UNIVERSITAS WIDYA HUSADA SEMARANG - Novita Alfiani; Ester Gita Kartika; Karina Cornelya Putri; Nindya Zahra Amelia; Afrina Imelia Napitupulu (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
According to the International Federation of Gynecology and Obstetrics, pregnancy is defined as the fertilization or union of a spermatozoon and an ovum, followed by nidation or implantation. A normal pregnancy, calculated from fertilization until birth, lasts 40 weeks. Pregnancy is divided into 3 trimesters: the first trimester lasts 12 weeks, the second trimester lasts 15 weeks (weeks 13 to 27), and the third trimester lasts 13 weeks (weeks 28 to 40). Objective: This community service aims to address and prevent musculoskeletal issues and pelvic floor dysfunction commonly occurring during pregnancy and the postpartum period. Methods: The community service activities were conducted through interviews regarding subjective complaints, direct surveys, and presentations on appropriate prenatal and postnatal exercises. Evaluation was carried out using pre-tests and post-tests, as well as weekly exercise observations. Results: The conducted counseling activities indicated a change in the mothers' level of understanding. Conclusion: Structured prenatal and postnatal exercises are effective for providing education, early detection, and support to improve maternal and child health.